Osmotic Dehydration of Fruits - Guiné, Raquel (2013)
The need for increasing improvements in the quality of food products conducted to an increased interest in osmotic treatment. This technology involves the partial dehydration of a water-rich solid foodstuff, either whole or in pieces, through immersion in an osmotic solution. In fact, osmotic treatment is applied with the goal of modifying the composition of food material through partial water removal and impregnation of solutes, without affecting the structural integrity of products. Three kinds of osmotic treatments have been used, depending on the pressure applied on the system: OD (osmotic dehydration at atmospheric pressure), VOD (osmotic dehydration at vacuum pressure) and PVOD (pulsed vacuum osmotic dehydration). However, the most common are OD and VOD technologies. Some of the potential applications of osmotic treatment in food technology include: (i) the development of compositionally formulated products by introducing functional food ingredients, such as firming agents, antioxidants, antimicrobial and nutraceuticals; (ii) preserving color, texture, natural flavor and aroma and any heat-sensitive nutrient components; and (iii) pre-treatment before freeze-drying for improving final product quality. However, the osmotic treatment on this wide range of applications requires an appropriate choice and control of operating conditions, such as processing temperature, pressure, time, composition, geometry of the food pieces and contact between the food pieces and the solution. The purpose of this chapter is to analyze the main effects of operating conditions and responses of the porous fruits to osmotic treatment, both at atmospheric and vacuum pressure, and to describe the important developments related to this technology in the fruit industry. Quality aspects of osmotic treatments on processed fruits, as well as technical challenges of this technique will also be discussed.